Efektivitas Fiskal - Moneter: Strategi Pemulihan Ekonomi Provinsi Riau Dalam Menghadapi Era New Normal - Dwi Widiarsih; Ranti Darwin; Khairi Murdy (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This research use an empirical test of long-term balance and co-integration between macroeconomic variables, fiscal policy and monetary policy. Fiscal policy is represented by government spending variables, while monetary policy is represented by the money supply. This study uses the Vector Error Correction Model (VECM) method. The research variables are economic growth, government spending and the money supply. The research period uses the period 2010-2019. The data quality test used the unit root test with the Augmented Dickey Fuller test (ADF) method, to see the empirical data stationarity and the cointegration value of the variables. The research shows that the data is stationary in first difference. Based on the results of the VECM test, it can be concluded that there is a stable long-term relationship between variables and the research model. The results of data processing showed that the most effective policy for changing economic growth in Riau Province was fiscal policy, namely government spending. This can be seen from the contribution of fiscal policy to the variability of economic growth which is the largest compared to the contribution of monetary policy